Reforming medical education admission and training in low- and middle-income countries: who gets admitted and why it matters - Katherine Tumlinson; Dilshad Jaff; Barbara Stilwell; Dickens Otieno Onyango; Kenneth L. Leonard (BMC, 2019)
Abstract Recent studies reveal public-sector healthcare providers in low- and middle-income countries (LMICs) are frequently absent from work, solicit informal payments for service delivery, and engage in disrespectful or abusive treatment of patients. While extrinsic factors may foster and facilitate these negative practices, it is not often feasible to alter the external environment in low-resource settings. In contrast, healthcare professionals with strong intrinsic motivation and a desire to serve the needs of their community are less likely to engage in these negative behaviors and may draw upon internal incentives to deliver a high quality of care. Reforming medical education admission and training practices in LMICs is one promising strategy for increasing the prevalence of medical professionals with strong intrinsic motivation.